Knowledge and Utilization of Preconception Care Among Pregnant Women Admitted in Antenatal Ward at Birat Medical College Teaching Hospital, Morang - Sharma, Ruby; Pokhrel, Sujita; Bhattarai, Amrita; Raut, Anisha; Mishra, Anjali (Birat Journal of Health Sciences, 2024)
Introduction: Preconception care is the provision of biomedical, behavioral and social health interventions to women and couples before conception occurs. It aims at improving health status and reducing behaviors and individual and environmental factors that could contribute to poor maternal and child health outcomes.Objectives: The objectives of the study were to find out the prevalence of knowledge and utilization of preconception care and to find out the association between knowledge and utilization of preconception care and selected sociodemographic, personal and social factors of the pregnant women.Methodology: An observational descriptive prospective cross-sectional study was conducted in the antenatal ward of Birat Medical College Teaching Hospital from 20th November 2023 to 16th February 2024 using a semi structured self developed questionnaire. One to one interview was done with the pregnant women and the collected data was entered in MS Excel and converted in to SPSS 25 for statistical analysis. For descriptive analysis mean, standard deviation, range, percentage proportion was calculated. Test of  association was done using Chi‑square, with the level of significance set at P < 0.05.Results: One hundred sixty (69.9%) pregnant women were of age 20-29 years. Their mean age was 25.82 years with the range of 16-38 years. Ninety five (41.5%) of them were Janajatis. Seventy one (31.0%) had the education up to Intermediate/Diploma level. More than half (69.4%) of the respondents were unemployed. Less than half (48.5 %) of them had family income per month above 30000. Majority (98.7%) were married. Though 58.5% of the women had moderate knowledge regarding preconception care, only 29.7% of them had utilized the Preconception care services. There was significant association between pregnant women’s age and knowledge of preconception care. Also there was association between respondent’s perception on importance of preconception care and its utilization. Conclusion: Even though having moderate knowledge women hadn’t used the preconception care and counseling services. This reveals a significant gap between knowledge and utilization of Preconception care which would impact the maternal and fetal outcome.